Ultrasonographic diagnosis of bilateral partial rupture of the infraspinatus muscle in a racing greyhound - Mestieri, Maria Ligia de Arruda; dos Santos, Bruna Gonzalez; da Silva, Mayara Nóbrega Gomes; Pascon, João Paulo da Exaltação; Carneiro, Leandro Ziemer (Brazilian Journal of Veterinary Medicine, 2021)
Athletic dogs are more susceptible to musculoskeletal disorders, especially in the muscles or tendons surrounding the shoulder joint. In this report, we describe a case of partial bilateral rupture of the infraspinatus muscle, an unusual injury. Clinical signs included lameness of the left thoracic limb after training. On physical examination, there was discomfort on bilateral palpation in the infraspinatus fossa region. The main clinical suspicion was partial rupture or myositis of the infraspinatus muscle (IF). Ultrasound examination of the region revealed the presence of hypoechoic areas intermingling the muscle fibers in a deeper and distal region of the infraspinatus muscle, compatible with edema or bilateral intramuscular hematoma (left +++, right ++) and integrity of the fascia. The findings were characterized as a partial rupture of the musculature. A detailed physical examination associated with ultrasound examination is essential for early diagnosis and therapeutic management. Although no other reports of partial rupture of the IF have been found, partial or complete rupture of muscle fibers in sport dogs is frequent. Early diagnosis prevents the development of contractures due to the institution of therapy before the fibrous process is established and improves prognosis.